Comparative Analysis of Fetal Kidney Length, Descending Colon Diameter, and Arterial Indices in Intrauterine Growth Restriction Versus Normal Growth Fetuses: A Case-control Study - abdolrazagh Nejad, Haniye; Mohammadifard, Mahyar; Mirgholami, Alireza; Bijary, Bita (Galen Medical Journal, 2025)
Background: Intrauterine growth restriction (IUGR) refers to poor fetal growth characterized by a multitude of neonatal complications, necessitating timely diagnosis and intervention. This study aimed to compare the descending colon diameter and kidney length between fetuses with IUGR and normal growth. Materials and Methods: In this case-control study, a total of 60 participants, 30 pregnant women with IUGR fetuses and 60 women with normal fetuses, referring to an institutional tertiary hospital in eastern Iran, in 2023, were surveyed. Variables included demographic data, fetal kidney length, descending colon diameter, and the pulsatility index (PI) and resistance index (RI) of maternal and fetal arteries. Statistical analysis was performed using IBM SPSS 18.0, with a significance threshold of P<0.05. Results: A total of 90 pregnant women with a mean age of 29.50 ± 6.61 years were included. The prevalence of patients with occupational employment was significantly higher in the IUGR group (P=0.012). The mean right and left kidney lengths and the anteroposterior diameter of the renal pelvis were significantly higher in normal fetuses compared to those with IUGR (P<0.05). However, no significant difference was found in descending colon diameter between the two groups (P=0.071). The RI and PI of the umbilical and uterine arteries were significantly higher in IUGR fetuses, while the RI and PI of MCA were higher in normal fetuses (P<0.05). Conclusion: Descending colon diameter is not a reliable marker for IUGR diagnosis. However, the use of RI and PI of umbilical, uterine, and cerebral arteries can be effective in identifying IUGR.